8=3(x-1)-(x-7)

Simple and best practice solution for 8=3(x-1)-(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8=3(x-1)-(x-7) equation:


Simplifying
8 = 3(x + -1) + -1(x + -7)

Reorder the terms:
8 = 3(-1 + x) + -1(x + -7)
8 = (-1 * 3 + x * 3) + -1(x + -7)
8 = (-3 + 3x) + -1(x + -7)

Reorder the terms:
8 = -3 + 3x + -1(-7 + x)
8 = -3 + 3x + (-7 * -1 + x * -1)
8 = -3 + 3x + (7 + -1x)

Reorder the terms:
8 = -3 + 7 + 3x + -1x

Combine like terms: -3 + 7 = 4
8 = 4 + 3x + -1x

Combine like terms: 3x + -1x = 2x
8 = 4 + 2x

Solving
8 = 4 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
8 + -2x = 4 + 2x + -2x

Combine like terms: 2x + -2x = 0
8 + -2x = 4 + 0
8 + -2x = 4

Add '-8' to each side of the equation.
8 + -8 + -2x = 4 + -8

Combine like terms: 8 + -8 = 0
0 + -2x = 4 + -8
-2x = 4 + -8

Combine like terms: 4 + -8 = -4
-2x = -4

Divide each side by '-2'.
x = 2

Simplifying
x = 2

See similar equations:

| 21-4b=13 | | K+3=11 | | 3(2x-2)-3=3(x-4)+30 | | 9(j+5)=99 | | 4/5v=28 | | 6x-(8x+7)=6x-15 | | 25x+63=13x-65 | | 5y-11=44 | | 3+3d=12 | | 3=9-2r | | 3(x-1)+4=2x | | P-4=1+3p+3p | | cos^2x+sin^2x= | | 2a+15=3a-18 | | (-4m^2+3n^2-5n)-[(3m^2-5n^2+2n)+(-3m^2)+4n^2]= | | -sin^2x+cos^2x= | | 2x+15+3x+5=6x-37 | | 9x+729=0 | | M=yi | | 10x-12=3x+11 | | -5x-10=q | | 2w^2+21w-180=0 | | b^-2/b^4 | | 8z^2-3z-5z^2-4z= | | 9x-2=-3 | | Z-z-z+z= | | 7x+5-5x=-11-6x | | (5x+3)(2x+25)=1406 | | 3x-5=-8(5n+6) | | 25x-14+7x+2=180 | | X-.25x=840 | | x+-6x-3=30 |

Equations solver categories